The effect of acetone dilution towards the surface topography and morphology of micro bearing concept for epoxy filled UHMWPE composite / Ahmad Aizuddin Ariffin ... [et al.] - Ariffin, Ahmad Aizuddin; Nik Ibrahim, Nik Noor Idayu; Shuib, Solehuddin; Romli, Ahmad Zafir; Ismail, Nur Faiqa (Penerbit UiTM (UiTM Press), 2019)
Surface topography and morphological behaviours are the important aspects in the application of surface bearing as it deals with the contact area of objects upon motion. Improved surface bearing will be set as an indicator for tribology behaviour to reduce the possibility of wear rate and reduce the friction of objects, respectively. Thus, in this study, the fundamental of micro bearing concept was imparted as the Ultra High Molecular Weight Polyethylene (UHMWPE), which is a low density filler, will float onto the surface of the composite system to become a solid lubricant upon curing. UHMWPE filler, which is commonly known for its dominant properties of high tendency to resist wear and has low coefficient of friction were fabricated alongside epoxy resin in the composite system to achieve the desired strength and durability to perform over time. However, there are limitations of UHMWPE during processing upon the dispersion of the fillers with the matrix particles due to epoxy resin that has relatively high in viscosity. Therefore, acetone has been selected as a diluent with ratio of 1:1/4, 1:1/3, 1:1/2, 1:1 to dilute the high viscosity epoxy resin. The surface profile measurement were examined using Alicona Infinite Focus and Polarised Optical Microscope. Based on the results observed, EpUPE3 (epoxy and UHMWPE with acetone ratio of 1:1/2) showed better surface distribution and morphology with relatively low value of surface roughness (Ra) which is 1.41 μm and low pseuodocolour value of surface height which is around 6.76-6.77 cm compared to other formulation ratio. In near future, these surface topography and morphological analysis are important to relate with tribological, physical and mechanical properties of the micro bearing layers for bearing applications, specifically.